Answer:
For the second image the answer is 1.2
Step-by-step explanation:
The others won’t load in ;-;
Answer:
C. -3, 3, -3, 3, ...
Step-by-step explanation:
-3×-3 = 3
3×-3 = -3
etc...
Hope this helps! :)
Answer:
![\begin{bmatrix}-2\\0 \end{bmatrix}](https://tex.z-dn.net/?f=%5Cbegin%7Bbmatrix%7D-2%5C%5C0%20%5Cend%7Bbmatrix%7D)
Step-by-step explanation:
We have the product,
.
It is known that,
'When we multiply a scalar with a matrix, the scalar is multiplied by each element of the matrix'.
So, we get,
.
⇒ ![\begin{bmatrix}-1\times 2\\0\times 2 \end{bmatrix}](https://tex.z-dn.net/?f=%5Cbegin%7Bbmatrix%7D-1%5Ctimes%202%5C%5C0%5Ctimes%202%20%5Cend%7Bbmatrix%7D)
⇒ ![\begin{bmatrix}-2\\0 \end{bmatrix}](https://tex.z-dn.net/?f=%5Cbegin%7Bbmatrix%7D-2%5C%5C0%20%5Cend%7Bbmatrix%7D)
So, the resulting product is
.